2018
DOI: 10.1177/1687814018776059
|View full text |Cite
|
Sign up to set email alerts
|

Uneven distribution characteristics of contact force of large-sized non-asbestos brake pad

Abstract: Large-sized non-asbestos brake pad is used in the brake system of mine hoister. During the braking process, uneven contact force distribution in the contact surface will occur, which accordingly leads to uneven wear and a shortened service life of the brake pad. To reveal contact force variation laws of large-sized brake pad during the braking process, using the software package ADINA, the braking process was simulated in this work. The results show that (1) the contact forces gradually present saddle-shaped d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Qingrui et al investigated the nonuniform wear and shorter lifespan of sizable nonasbestos brake pads. The brake pad was modeled and simulated on the ADINA software, and simulations were carried out to find the effects of radius, pressure, velocity, and temperature on the wear characteristics of the pads [10]. Results showed that the nonuniform distribution of temperatures and contact forces leads to uneven surface wear of the pads, thereby reducing the stability of the brake pads.…”
Section: Introductionmentioning
confidence: 99%
“…Qingrui et al investigated the nonuniform wear and shorter lifespan of sizable nonasbestos brake pads. The brake pad was modeled and simulated on the ADINA software, and simulations were carried out to find the effects of radius, pressure, velocity, and temperature on the wear characteristics of the pads [10]. Results showed that the nonuniform distribution of temperatures and contact forces leads to uneven surface wear of the pads, thereby reducing the stability of the brake pads.…”
Section: Introductionmentioning
confidence: 99%